Perspectivas críticas na pesquisa sobre formação de professores de Ciências - Luciana Maria Lunardi Campos [UNESP]; Renato Eugênio da Silva Diniz [UNESP]; Moises Nascimento Soares [UNESP]; Maria de Lourdes Spazziani [UNESP]; Andrea Vassallo Fagundes [UNESP]; Camila Silveira da Silva [UNESP]; Fabricio Vieira de Moraes [UNESP; Raquel Sanzovo P. de Campos [UNESP]Sabrina Pereira S. Basso [UNESP] (My University, 2013)
This text is in theoretical study, with consideration of the authors of the critical perspective of education and training of science teachers. We indicate a set of principles and concepts of some philosophers, like Habermas and Gramsci and theoretical education in a critical bias, as Freire, Saviani, Giroux and Duarte, which can enrich the discussions in the field of science teacher education. Some of these concepts: organic intellectual philosophy of praxis, inconclusiveness, incompleteness, dialogue and problematization, communicative action, critical pedagogies of learning to learn, dialectical relationship between theory, culture and depth psychology. Thus, we intend to explain the richness of the dialogue among this perspective and its implications for the training of science teachers.

Este texto constitui-se em estudo teórico, apresentando considerações sobre autores da perspectiva crítica de educação e a formação de professores de Ciências. Indicamos um conjunto de princípios e conceitos de alguns filósofos, como Habermas e Gramsci e teóricos da educação num viés crítico, como Freire, Saviani, Giroux e Duarte, que possam enriquecer as discussões no campo da formação docente de ciências. Alguns desses conceitos são: intelectual orgânico, filosofia da práxis, inconclusividade, inacabamento, dialogicidade, problematização, ação comunicativa, crítica as pedagogias do aprender a aprender, relações dialéticas entre teoria, cultura e psicologia profunda. Dessa forma, pretendemos explicitar a fecundidade da maior interlocução entre tal perspectiva e suas implicações para a formação de professores de ciências.
Critical perspectives on education and science teacher education: a theoretical study
Keywords: Critical Perspectives; Teacher Education; Theoretical Study; Perspectivas Críticas; Formação de Professores; Estudo Teórico